ANALISIS TINGKAT KEPUASAN PELANGGAN PADA JASA DEKORASI PERNIKAHAN DENGAN METODE SERVICE QUALITY (SEVQUAL) DAN IMPORTANCE PERFORMA ANALYSIS (IPA) (STUDI KASUS : RUSTIC DECORATION MEDAN) - Sibuea, Siti Rahmah; Arfah, Mahrani; Tarigan, Fachriza Ikhsan (Universitas Islam Sumatera Utara, 2026)
This study aims to evaluate the level of customer satisfaction with the quality of service provided by the Rustic Decoration Medan (RDM) wedding decoration service company. This study is motivated by the absence of a systematic evaluation of service quality during the five years of RDM's operation, even though the dynamics of competition in the decoration industry are increasing. This study uses a quantitative approach using the SERVQUAL method to measure 5 dimensions of service quality, namely tangible, reliability, responsiveness, assurance, and empathy. In addition, Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) are used to map improvement priorities and assess satisfaction levels comprehensively. Data collection was carried out by distributing questionnaires to 50 respondents who were active customers in the period October to December 2024. The results of the analysis showed that the reliability dimension had the lowest level of conformity of 65%, while the empathy dimension obtained the highest level of conformity of 88.88%. The customer satisfaction index (CSI) value of 39.66% indicates that customer expectations have not been optimally met. The findings in quadrant I of IPA place the aspects of punctuality and employee responsiveness as the main priority for improvement. The results of this study are expected to provide strategic contributions to the management of RDM services and become a reference for improving service quality in the wedding decoration service sector